Political Awakening of Youth in Democracy - Sriruksa, Chokchai (Journal of MCU Phetchaburi Review, 2022)
Political development in a democratic system in today's society will develop advancement in thinking, both intellectually and there are many people of different classes who are alert in politics in democratic systems at both the youth and new generation level and the people's level. All ages, especially youths with high political alertness in democratic regimes and high individuality in developing politics to become a democratic system. because there is a need for rights Freedom and equality and justice are truly transparent. Since the first day that student groups organize "flash mob" activities to demand democracy. anti-government including expressing disagreement with the Constitutional Court's decision to dissolve the Future Forward Party Demonstrations have taken place in several educational institutions across the country over the past year and are now still demanding to oust the government from the dictatorship. And society pays attention to the phenomenon of the new generation coming out of this political movement, not least There are both those who support and question the "behind the scenes" of the new generation's gathering. Some say they were instigated or have a political party backing the BBC Thai asking students-students why he and she came out to rally. And is there anyone behind the movement.